Evaluating Strength Characteristics of Pavement by Using Reclaimed Asphalt Pavement (RAP) - Ankur Malik, Satnam Singh, Sandeep Singh (International Journal of Advanced Science and Technology, 2020)
A good transportation network is a key for the industrialization and growth of the nation and in response, the needs of the road users are increasing day by day. The peak hour traffic on roads contributes to damage the surface and pavement. Sometimes it is observed that the road fails during the construction or before completing their design life. For the damaged sections re-surfacing is required, the top layer is scratched off and the scratched material from the top or the blacktop is utter a waste and is dumped off to the sites. This byproduct which contains asphalt and aggregates is collected and reprocessed by adding desirable quantity of bitumen and other minerals for resurfacing and is called as Reclaimed Asphalt Pavement (RAP). This paper investigates the use of the RAP in the pavement materials partially or as a substitute of some material up to certain rate and thus relative strength of the pavement is evaluated.